The pattern making of mega-slums on semantics in slum urban cultures - Zappulla, Carmelo; Suau, Cristian; Fikfak, Alenka (Journal of Architecture and Urbanism, 2014)
Mega-slums are dynamic laboratories for urban pattern making. Instead of surveying about stable urban symbols represented by formal orders and regular geometries, this study explores the semantic meaning of informal urbanism associated with chaos or randomness and often ignored by critique and conventions. Slums are forms of ‘instant urbanity’ that underscore alternative ways of self-organisation, which include bottom-up strategies, autonomous urban dynamics and spatial activation by remaking.Are slum patterns representing a lack of symbolism or, on contrary, rich, complex, and fluid urban idioms? Urban informality without planning offers immense opportunities to investigate resilient urban forms and languages as complex systems throughout self-ruled structures. Slums are not only the result of urban economic asymmetries and social marginalisation but the elementary construction of survival urbanism, a randomised, agile and transformative pattern system.Slum making is a form of subsistence urbanity that constructs transitory, elusive or spontaneous geometries. They differ in sizes, magnitudes and geometries regarding cultural, climatic and topographic conditions. Slums are unstable systems in continuous transformation. This essay questions the stigmatisation of informalised urban patterns as ‘other’ unclassified codes by analysing a selection of twenty mega-slums in the Americas, Africa and Asia regarding semantics, urban and geometrical meanings. Their urban tissues contain various symbols that activate the every-day production of spaces. They can be visible or invisible; passive or active; and formal or informal. A taxonomic tree of slums was developed to compare and map slum regions to describe similarities and differences among the selected case studies. From this analysis, a profound discourse appeared between informal settlements: tissue-patterns at macro level and cell-patterns in micro urbanisation. Does the macro pattern inform the micro, or vice versa?